2011
DOI: 10.3233/jad-2011-110161
|View full text |Cite
|
Sign up to set email alerts
|

Tau Transgenic Mice as Models for Cerebrospinal Fluid Tau Biomarkers

Abstract: Levels of tau in cerebrospinal fluid (CSF) are elevated in Alzheimer's disease (AD) patients. It is believed this elevation is related to the tau pathology and neurodegeneration observed in AD, but not all tauopathies have increased CSF tau. There has been little pre-clinical work to investigate mechanisms of increased CSF tau due to the difficulty in collecting CSF samples from mice, the most commonly used pre-clinical models. We developed methods to collect CSF from mice without contamination from tau in bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 46 publications
9
81
0
Order By: Relevance
“…2 D). Tau-P301L transgene expression can be reduced 75% in rTg4510 mice with doxycycline treatment Barten et al, 2011), which was also observed in this study by immunohistochemical staining of tau (Fig. 3A).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…2 D). Tau-P301L transgene expression can be reduced 75% in rTg4510 mice with doxycycline treatment Barten et al, 2011), which was also observed in this study by immunohistochemical staining of tau (Fig. 3A).…”
Section: Resultssupporting
confidence: 87%
“…Abnormal MT turnover in the two transgenic lines was generally consistent with the level of tau pathology not just total tau protein levels. 3xTg mice have approximately twofold overexpression of the tau-P301L transgene and much less pathology than the 13-fold overexpressing rTg4510 line Barten et al, 2011). Even so, Tau Alone transgenic mice have leaky transgene expression from the TRE promoter that is close to the amount observed in 3xTg mice.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Tau is constitutively released from neurons under physiological conditions [71,[76][77][78][79][80][81][82][83][84][85][86][87][88]. The secretion is multifaceted, involving diverse intracellular components such as autophagosomes, Golgi, endosomes, ectosomes, lysosomes, microsomes and endoplasmic reticulum [89]. In the diseased brain, extracellular tau additionally originates from dead or dying neurons as well as a result of active secretion [76,90] and yet unknown mechanisms.…”
Section: Mechanisms Of Tau Release and Spreadingmentioning
confidence: 99%